Free Fibular Osteoseptocutaneus Flap for Reconstruction Giantameloblastoma - Rachmat Wiardi; Irra Rubianti W (Fakultas Kedokteran Universitas Riau, 2015)
Ameloblastoma is a tumor originating from odontogenic epithelial cells. The tumor is located in the gray zone betweenbenign and malignant neoplasms. These tumors can occur at any age. Although traditionally divided as solid andcystic ameloblastoma, nearly all showed cystic changes. These tumors are invasive and have a very high recurrencerate. Ameloblastoma is an odontogenic tumor that is often found. These tumors are generally diagnosed in the fourthand fifth decade. Approximately 80% of these tumors occur in the jaw, with three-quarters are in the molar region andramus. Approximately 20% of them occurred in the premolar and incisivum. Operative therapy was elected a radicalresection of the affected parts of the jaw, followed by reconstruction. Bridging titanium plate can be used to replacepart of lost bone and serves as a means of reconstruction. Various methods of reconstruction of the mandible can bedone by using a bone graft from the calcaneus, fibula, ribs, scapula, iliac crest, or flap reconstruction. We report acase of male patients at entry RSHS Hospital May 11, 2010 18 years old with complaints arising the lump under thetongue ± 8 years ago, accompanied by difficulty eating, difficulty speaking, and shortness of breath. Patients in thediagnosis of ameloblastoma of the mandible on the basis of anatomic pathology examination. It was decided to do thereconstruction of segmental mandibulectomy and free fibular osteoseptocutaneous free flap with multiple osteotomy.Patients go home in improvement condition.